Clock Drawing Performance Slows for Older Adults After Total Knee Replacement Surgery. (July 2019) - Hizel, Loren P.; Warner, Eric D.; Wiggins, Margaret E.; Tanner, Jared J.; Parvataneni, Hari; Davis, Randall; Penney, Dana L.; Libon, David J.; Tighe, Patrick; Garvan, Cynthia W.; Price, Catherine C.
Abstract : BACKGROUND: Clock drawing is a neurocognitive screening tool used in preoperative settings. This study examined hypothesized changes in clock drawing to command and copy test conditions 3 weeks and 3 months after total knee arthroplasty (TKA) with general anesthesia. METHODS: Participants included 67 surgery and 66 nonsurgery individuals >60 years who completed the digital clock drawing test before TKA (or a pseudosurgery date), and 3 weeks and 3 months postsurgery. Generalized linear mixed models assessed digital clock drawing test latency (ie, total time to completion, seconds between digit placement) and graphomotor output (ie, total number of strokes, clock size). Reliable change analyses examined the percent of participants showing change beyond differences found in nonsurgery peers. RESULTS: After adjusting for age, education, and baseline cognition, both digital clock drawing test latency measures were significantly different for surgery and nonsurgery groups, where the surgery group performed slower on both command and copy test conditions. Reliable change analyses 3 weeks after surgery found that total time to completion was slower among 25% of command and 21% of copy constructions in the surgery group. At 3 months, 18% of surgery participants were slower than nonsurgery peers. Neither graphomotor measure significantly changed over time. CONCLUSIONS: Clock drawing construction slowed for nearly one-quarter of patients after TKA surgery, whereas nonsurgery peers showed the expected practice effect, ie, speed increased from baseline to follow-up time points. Future research should investigate the neurobiological basis for these changes after TKA.